2012
DOI: 10.4103/2152-7806.97007
|View full text |Cite
|
Sign up to set email alerts
|

Unusual growth pattern of a meningioma

Abstract: Background:Rhabdoid meningioma exhibits high mitotic activity, anaplasia, and increased markers of cell proliferation. Here we describe a rhabdoid meningioma with a pattern of growth extending into the subarachnoid space and filled the cortical sulci.Case Description:A 72-year-old woman presented with headache and was admitted to our hospital. Neurologic and physical examinations revealed no abnormalities. Contrast-enhanced axial T1-weighted images showed a well-enhanced, dural-based mass compressing the right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…First, we performed a deep review of RM cases previously reported in the literature between 1998 and 2021 [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 ]. A total of 305 RM cases were identified, including adults and children or adolescents under the age of 18 years.…”
Section: Methodsmentioning
confidence: 99%
“…First, we performed a deep review of RM cases previously reported in the literature between 1998 and 2021 [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 ]. A total of 305 RM cases were identified, including adults and children or adolescents under the age of 18 years.…”
Section: Methodsmentioning
confidence: 99%